2010
DOI: 10.1021/nn1013337
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchic Self-Assembly of Nanoporous Chiral Networks with Conformationally Flexible Porphyrins

Abstract: We report the hierarchic design of homochiral 2D nanoporous networks under ultrahigh vacuum conditions on the Ag(111) surface by using a flexible porphyrin derivative as a primary unit. The conformational adaptation of the molecular module gives rise to two enantiomers upon 2D confinement, which self-assemble in enantiopure clusters made of three molecules reflecting chiral recognition, which constitute the secondary supramolecular building block mediating the formation of the tertiary complex open networks. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 52 publications
3
50
1
Order By: Relevance
“…4, a purely rotational step is not possible for sterical reasons as indicated by the dotted circle in structure i if one assumes that the molecule is rigid and the molecule is confined to two dimensions, i.e., all parts of the molecule are always in contact with the surface. Even if one takes into account that the ethynyl bonds exhibit considerable flexibility, [63][64][65][66] they would have to be deformed to an extent (more than 60°) which seems unreasonable (structure ii). Including the third dimension by allowing the molecule to partially detach, the deformation of the molecule during a rotational step can be limited to its normal flexibility by one arm passing above a PTCDI molecule (structure iii).…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…4, a purely rotational step is not possible for sterical reasons as indicated by the dotted circle in structure i if one assumes that the molecule is rigid and the molecule is confined to two dimensions, i.e., all parts of the molecule are always in contact with the surface. Even if one takes into account that the ethynyl bonds exhibit considerable flexibility, [63][64][65][66] they would have to be deformed to an extent (more than 60°) which seems unreasonable (structure ii). Including the third dimension by allowing the molecule to partially detach, the deformation of the molecule during a rotational step can be limited to its normal flexibility by one arm passing above a PTCDI molecule (structure iii).…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…13,[24][25][26][27] Recently, special attention has been devoted to systems presenting a hierarchical chirality transfer, which reveals the presence of sequentially-activated enantioselective mechanisms. 24,[28][29][30][31][32][33][34][35] Blüm et al 28 reported the fascinating case of rubrene (C 42 H 28 ) assembling into pentagonal structures, which act as building blocks for a second generation decagons. Interestingly, both the resulting supramolecular structures are enantiopure, indicating the conservation of chirality during the coordination.…”
Section: Introductionmentioning
confidence: 99%
“…Hierarchical organization can also be steered through metal-ligand interactions, where the presence of metal adatoms imposes distinctive multilevel binding processes. 24,33 Furthermore, sequential self-assembly of nanoporous homochiral networks has been recently observed using porphyrin derivatives, 29 representing an appealing platform for the realization of flexible functional materials. However, the atomic-scale mechanisms driving molecular recognition in hierarchical assemblies are yet to be clarified and the factors governing the enantioselectivity of these processes are largely unknown, limiting the possibility to design a priori tailored molecular units with programmed functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…This is the reason why synthetic metalloporphyrin complexes are often used as analogues of natural systems found in photosynthesis, oxygen carriers, and catalysts [5] [9][10][11][12][13][14]. For instance, these systems are used to understand the mechanism of electron transfer through intermolecular interactions, and some works show that efficient energy transfer may occur across the intermolecular bonds [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%